Incidence of type 2 diabetes mellitus in persons living with HIV initiated on dolutegravir-based antiretroviral regimen in Ghana: an observational longitudinal study - Margaret Lartey; Ernest Kenu; Vincent Ganu; Stephen Ayisi Addo; Kofi Agyabeng; Delia Bandoh; Marijanatu Abdulai; Prince Tsekpetse; Kwasi Torpey (Journal of Health, Population and Nutrition)
Abstract Background Few studies have reported hyperglycemia and diabetic ketoacidosis in patients on dolutegravir (DTG) treatment. This study determined the effect of DTG on fasting blood glucose levels in a cohort of persons living with HIV (PLHIV) in Ghana and initiating DTG regimens. Methods A two-year observational longitudinal cohort study conducted from 12th October 2020 to 31st December 2022. Fasting blood glucose was measured at baseline, 12, 24, 36 and 72 weeks for patients after a 12 h overnight fast. The Kaplan-Meier estimator was used to estimate the risk of developing type 2 diabetes mellitus (T2DM). Cox proportional hazard model was used in estimating hazard ratios. Results A total of 1334 non-diabetic patients were enrolled with 78% (1039) females and 83% (1104) were antiretroviral therapy experienced. The incidence proportion and rate of T2DM at 72 weeks were 11.8% (95%CI: 10.2–13.7) and 98.1 cases per 1000 PY (95%CI: 83.9-114.6) respectively. The median time to development of T2DM was 24 weeks post DTG initiation. Male sex (aHR 2.9 [95%CI: 1.9–4.3]), abnormal waist-hip ratio (1.67 [95% CI: 1.15–2.43]) and abnormal total serum cholesterol (aHR 1.6 [95%CI: 1.1–2.3]) were found to be significant determinants of T2DM. Conclusion Incidence of T2DM is high among non-diabetic PLHIV within 72 weeks of initiating DTG based therapy with males having a higher risk. Longitudinal changes in waist-hip ratio and serum cholesterol among patients initiated on DTG needs to be monitored regularly.